Quest for Identity in Diasporic World of V. S. Naipaul’s Half a Life - Rai, Ram Prasad (Humanities and Social Sciences Journal, 2022)
This paper aims to explore the pursuit of identity in the diaspora in V. S. Naipaul’s Half a Life. Willie Somerset Chandran desires to establish himself as a writer, but his own father does not like his writing. He receives scholarship to study in London. There, too, he writes books, but he is discouraged by the publishers. Apart from this, he cannot live in London comfortably because of the strange culture and social activities unlike in India, his home country. In the South Africa, he realizes the loss of 18 years without developing his career and goes to live with his sister in Germany. He is in search of identity in the diaspora in different host lands. His mentality is never stable in the foreign lands as he is unsuccessful to maintain a certain identity that he wishes to have. However, his pursuit of identity continues in various host lands despite his failure. In this qualitative research work, the researcher applies the concept of 'identity' in diaspora theory in order to study the quest of identity of the main character Willie Chandran. Various journal articles and books in relation to diaspora, identity and Naipaul’s Half a Life have been consulted for the support of this research project. This study will certainly be helpful to the further researchers on the particular text and the diaspora theory.